PKM Pemanfaatan Cocopeat untuk Media Tanam pada Pembibitan Kakao - Ruli, Ketrin; Wahyuni, Yuyun; Beja, Henderikus Darwin (LPPM Universitas Flores, 2023)
This article presents the results of community service activities carried out in Bloro village, Nita Sub-district, Sikka district. This activity aims to overcome coconut fibre waste in Bloro village, especially in the Plea Puli farmer group. The solution to reducing this waste so that environmental pollution does not occur and does not cause dengue fever which can be detrimental to human health, is to use coconut fibre waste to make items of selling value and have useful properties, one of which can be processed into a planting medium in the form of cocopeat, using a natural process. Namely through grating or crushing. Cocopeat is a planting medium that is cheap, environmentally friendly and has many benefits. One of the benefits of cocopeat is it can be used as a planting medium that is resistant to fungus, able to store a lot of water, and can fertilize plants. Method for implementing the coconut fibre waste processing process which consists of (1) counselling, (2) direct practice, and (3) mentoring. From the use of cocopeat, it can be used as a planting medium for cocoa seedlings. To carry out seeding, it is necessary to select superior varieties, the varieties used in cocoa nurseries, namely clone Sulawesi 01. In carrying out seedlings, it is necessary to go through several stages, namely:(1) preparing the seed for sowing, (2) preparing the nursery, (3) preparing the planting medium, (4) planting, and (5) caring for the seed. From this activity, it can be concluded that nurseries using cocopeat can provide optimal growth and development. It is hoped that this activity can have a sustainable positive impact on the Bloro Village community, especially members of the plea puli farmer group and become an inspiring example for cocoa nurseries using cocopeat growing media.